Effectiveness of Islamic values-based problem-solving learning in enhancing social awareness in Islamic religious education subject - Arman Arman; Khairudin Khairudin; Sri Jamilah; Nordinah Wati (Fakultas Tarbiyah, Universitas Ibrahimy, 2026)
The rapid advancement of digital technology has contributed to increasing individualistic tendencies among adolescents. Meanwhile, IRE (Islamic Religious Education) remains predominantly conventionally oriented and has not adequately fostered students’ social awareness. Therefore, this study aims to examine the effectiveness of problem-solving learning integrated with Islamic values in enhancing students’ social awareness in IRE subjects. This study employed a quasi-experimental design involving 40 tenth-grade students from a vocational high school in Bima City, divided into an experimental group (n = 20) and a control group (n = 20). The experimental group received problem-solving instruction integrated with Islamic values, whereas the control group participated in conventional learning. Data were collected through validated and reliable pretests and posttests and analyzed using normality, homogeneity, and independent samples t-tests. The findings indicate that Islamic values–integrated problem-solving learning was significantly more effective in enhancing students’ social awareness than conventional instruction. The study further demonstrates that this learning model effectively promotes students’ cognitive understanding of social responsibility, including helping behavior, social harmony, empathy, and environmental awareness. The novelty of this research lies in the innovative design of IRE learning that integrates Islamic values into problem-solving activities to strengthen character education. Enhancing social awareness among vocational high school students is essential in preparing them to navigate the future dynamics of the workplace and industrial environments.